Physiological adaptation in women concurrently training for strength and endurance - Gravelle, B. L.; Blessing, D. L. (The Journal of Strength and Conditioning Research, 2000)
The purpose of this study was to compare the physiological responses of 19 active women to 11 weeks of concurrent strength and endurance training or strength training only. Six young women were assigned to group lift-row (LR), in which weight training was followed immediately by endurance training, while another group, row-lift (RL, n = 7) performed endurance training before strength training. A third group, lift only (LO, n = 6), participated in only strength training. Endurance training (rowing) was performed 3 times per week for 45 minutes at 70% o2max. Strength training consisted of 45 minutes of 5-6 lower-body exercises designed to increase strength. Results indicated that 1 repetition maximum leg press increased p 26.6, 27.4, and 25.9% (p < 0.05) for the LR, RL, and LO groups, respectively. Only the LR group experienced increases in peak anaerobic power, anaerobic capacity (ANC), and relative ANC. However, no differences in power measures were detectable among groups at the conclusion of training. Maximum heart rate (MHR) and maximum oxygen uptake (o2max) increased for all groups from pre- to posttraining but reached significance for the LR and LO groups only with no between-group differences. Percentage of body fat and time to exhaustion during the o2max test manifested no pre- to posttraining or intergroup differences. The present results do not emonstrate any negative effects on strength development for women concurrently training for strength and endurance. Furthermore, the sequence or order of training did not influence strength training adaptations but may have limited aerobic adaptations.